Study on performance-centric offload strategies for LTE networks - Hagos, Desta Haileselassie; Kapitza, Rüdiger (Proceedings of 2013 6th Joint IFIP Wireless and Mobile Networking Conference, WMNC 2013, 2013)
Currently, cellular networks are overloaded with mobile data traffic due to the rapid growth of mobile broadband subscriptions and the increasing popularity of applications for smartphones. One possible solution to alleviate this problem is the offloading of mobile data traffic from the primary access technology to the WiFi infrastructure to gain extra capacity and improve the overall network performance. As the strategy what and when to offload data is non-trivial, it is of vital importance to develop novel algorithms to guide this process. This paper addresses solutions for WiFi offloading in Long Term Evolution (LTE) cellular networks when performance needs exceed the capability of the LTE access. It then compares the performance of each access technology using different network performance metrics. In detail, an optimized Signal-to-noise ratio (SNR)-threshold based handover solution and extension to the 3rd Generation Partnership Project (3GPP) standard for Access Network Discovery and Selection Function (ANDSF) framework for WiFi offloading is proposed. Our simulation results have shown that ANDSF discovery can be used to control the amount of offloading. © 2013 IEEE.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Access Selection; ANDSF; IEEE 802.11; LTE; multi-access; Offloading; Seamless Handover; WiFi Access Points